Effectiveness of Massive Open Online Course on Risk Communication Knowledge in Global Health Emergencies Among Nurses - Khin Thandar Aung; Rafiza Abdul Razak; Muhammad Fadli Zulkafley (Jurnal Keperawatan Indonesia, 2024)
Massive Open Online Courses (MOOCs) have transformed education. The minimal usage of MOOCs in nursing education reveals a lack of continuous healthcare professional development. Although MOOCs are recognized as a viable means of continuing education for healthcare professionals, their application and content specifically tailored to healthcare have remained unexplored. This study aimed to determine the effectiveness of a dedicated Massive Open Online Course (MOOC) designed to enhance nurses' risk communication knowledge in global health emergencies through testing with a small nurse sample in a pilot trial. This preliminary examination seeks participant feedback and insights. A quasi-experimental research design was conducted, employing a one-group pre-test and post-test design using the convenience sampling method with 40 registered nurses from the medical center of International Islamic University Malaysia. These nurses engaged in a four-week MOOC hosted on i-Taleem (the university's eLearning platform), focusing on knowledge about risk communication. Pre- and post-course questionnaires were administered, and the data was analyzed using SPSS version 20.0's paired t-test. The study showed a significant improvement in test scores with a p-value of 0.022, which is less than the predetermined significance level of 0.05. Consequently, the alternate hypothesis (HA) is accepted, signifying a substantial improvement in nurses' knowledge of risk communication in global health emergencies. Additionally, this study provides the framework for the widespread implementation of such instructional interventions in nursing education and professional development. Keywords: global health emergencies, massive open online courses (MOOCs), nurse, risk communication   Abstrak Efektivitas Massive Open Online Course terhadap Pengetahuan Komunikasi Risiko di Kalangan Perawat dalam Keadaan Darurat Kesehatan Global.Massive Open Online Courses (MOOCs) telah mengubah pendidikan. Minimnya penggunaan MOOCs dalam pendidikan keperawatan menunjukkan kurangnya pengembangan profesional berkelanjutan di bidang kesehatan. Meskipun MOOCs diakui sebagai sarana yang layak untuk melanjutkan pendidikan bagi para profesional kesehatan, penerapan dan kontennya yang secara khusus dirancang untuk perawatan kesehatan masih belum dieksplorasi. Penelitian ini bertujuan untuk menentukan efektivitas kursus MOOC yang dirancang untuk meningkatkan pengetahuan komunikasi risiko perawat dalam keadaan darurat kesehatan global melalui pengujian dengan uji coba terhadap sampel perawat dalam skala kecil. Pengujian awal studi ini bertujuan untuk mengetahui umpan balik dan wawasan peserta. Desain penelitian kuasi-eksperimental menggunakan pre-test dan post-test satu kelompok dengan menggunakan metode convenience sampling terhadap 40 perawat terdaftar di pusat kesehatan universitas. Perawat ini terlibat dalam kursus MOOC selama empat minggu yang diselenggarakan di i-Taleem platform (platform eLearning universitas), memfokuskan pengetahuan tentang komunikasi risiko. Kuesioner pre- dan post-course diberikan, dan data dianalisis menggunakan Paired-T test SPSS versi 20.0. Studi ini menunjukkan peningkatan nilai yang signifikan dengan nilai p sebesar 0,022, lebih kecil dari tingkat signifikansi yang telah ditentukan yaitu 0,05. Alhasil, hipotesis alternatif (HA) diterima, menandakan peningkatan substansial dalam pengetahuan perawat tentang komunikasi risiko dalam keadaan darurat kesehatan global. Studi ini memberikan kerangka kerja untuk penerapan intervensi instruksional secara luas dalam pendidikan keperawatan dan pengembangan profesional. Kata Kunci: darurat kesehatan global, komunikasi risiko, massive open online courses (MOOCs), perawat